Treasury of Greek mythology : classic stories of gods, goddesses, heroes & monsters - Napoli, Donna Jo, 1948-; Balit, Christina (Washington, D.C. : National Geographic, 2011)
Presents illustrated retellings of classic Greek myths, sharing the stories of Zeus, Aphrodite, Apollo, Athena, Helen of Troy, Perseus, and Medusa, with sidebars for each god, goddess, hero, and monster that link the tales to constellations, history, geography, and culture, and including profiles, a family tree, and other resources.
Includes bibliographical references (p. 186-187) and index.
Kirkus Starred
School Library Journal starred
Kirkus Starred, September 2011
School Library Journal starred, October 2011
5.3
Keywords: Mythology, Greek -- Juvenile literature; Mythology, Greek; Greek mythology